Analisis Kualitas Pelayanan Pembayaran Pajak Kendaraan Bermotor (PKB) Melalui Layanan Samsat Keliling (Studi Kasus Pada Kantor Bersama Samsat Pamekasan) - Annisa, Suzan; M, Meirinawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Quality public services are key to increasing taxpayer compliance and optimizing Regional Original Revenue (PAD). The Mobile Samsat service at the Joint Samsat Office of Pamekasan serves as a solution to facilitate access to Motor Vehicle Tax (PKB) payments, especially for citizens living far from the main Samsat office. This service also operates during both daytime and nighttime hours, helping to reduce queues and support taxpayers with limited time. This study aims to analyze the quality of PKB payment services through the Mobile Samsat using a descriptive qualitative approach and Dwiyanto’s (2021) service quality theory, which includes five indicators: officer attitude, procedures, service time, facilities, and service costs. The results show that the overall service quality is fairly good and satisfactory. The attitude of the officers is excellent—friendly and professional. The procedures are simple and easy to understand, although information regarding service schedules and routes is still limited. Service time is fast, averaging only 2–5 minutes, even quicker than the standard. However, physical facilities such as waiting chairs are not yet available, and some service locations are less comfortable. Service costs are in accordance with applicable regulations. Therefore, the Joint Samsat Office of Pamekasan needs to improve supporting facilities, expand the dissemination of service schedules and routes, and evaluate service locations to ensure a more comfortable and conducive experience for taxpayers.